Chronic Itch Affects Patients' Ability to Experience Pleasure: Anhedonia in Itchy Disorders - Aleksandra Stefaniak; Magdalena Berek-Zamorska; Claudia Zeidler; Sonja Ständer; Jacek C. Szepietowski (Medical Journals Sweden, 2024)
Anhedonia, the reduced ability to experience pleasure, is a prevalent symptom in various psychiatric disorders, but has not been investigated in dermatological conditions, particularly those characterized by chronic itch. This study aimed to examine the prevalence and clinical correlates of anhedonia in patients with chronic itch. A cross-sectional study was conducted in 137 patients with chronic itch, classified according to the International Forum for the Study of Itch (IFSI) classification. Anhedonia was assessed using the Snaith-Hamilton Pleasure Scale (SHAPS) and Anticipatory and Consummatory Interpersonal Pleasure Scale (ACIPS). Itch severity, quality of life, and psychological distress were assessed using the Visual Analogue Scale (VAS), Verbal Rating Scale (VRS), ItchyQoL, and Hospital Anxiety and Depression Scale (HADS), respectively. The mean SHAPS score was 1.0 ± 1.7 points, and the mean ACIPS total score was 76.9 ± 16.2 points. In the study sample, 13.1% of patients were identified as anhedonic, with a higher prevalence observed in those with severe and very severe itch. Anhedonia was significantly correlated with itch severity (R = 0.2, p=0.02 for 24 h VASmean and SHAPS; R = 0.2, p = 0.01 for 24 h VASmax and SHAPS), anxiety symptoms (R = 0.3, p < 0.001 for SHAPS and HADS-anxiety), depression symptoms (R = 0.4, p < 0.001 for SHAPS and HADS-depression), and impairment in quality of life (R = 0.2, p = 0.014 for SHAPS and ItchyQoL). Anhedonia is a significant and prevalent aspect of psychological distress in patients with chronic itch. Addressing this symptom may not only improve patients' overall mental health but also enhance the effectiveness of treatments for chronic itch. Future research is needed to elucidate further the mechanisms underlying the relationship between anhedonia and chronic itch and to develop targeted interventions for this population.